WTO accession and socio-economic development in China - Basu, Parikshit K.; Bandara, Yapa M. W. Y. (Chandos Asian studies series., 2009)
This book reviews how China's accession to the WTO has impacted upon its education, environment, economic and social outcomes in recent years. It has been argued that China's rapid growth in output and exports and subsequent accession to WTO has significantly increased income and therefore the well-being of the Chinese population. However, doubts are now being raised that higher income is generated at the cost of deteriorating environmental and social standards which has increasingly affected the health of the Chinese people, especially those who live in major industrial cities. Also, there is a widespread perception that its accession to WTO has significantly increased social shocks, especially among the farming community, and contributed to poor health outcomes among the rural population. These issues are critically analysed in this book by experienced academics from China and Australia. Includes contributions from Australian and Chinese scholars and thus, brings together ideas and suggestions from a broad range of perspectivesAnalyses China's socio-economic challenges from a multi-dimensional focusA very useful reference in WTO issues in general and China in particular.